KEPEMIMPINAN KEPALA DESA TERHADAP PARTISIPASI MASYARAKAT MELALUI KEBIJAKAN PEMBERDAYAAN DI KECAMATAN NARINGGUL - Rachmat Rachmat; Neli Yuliawati; Dewi Siti Hendriani (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2026)
This study aims to analyze the influence of the Village Head's leadership on community participation, with village policy and empowerment acting as mediating variables in Naringgul District, Cianjur Regency. The method used is a quantitative approach with an explanatory research design. Data were collected through questionnaires from 85 respondents, determined using a proportionate stratified random sampling technique. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results show that the Village Head's leadership has a highly significant positive direct influence on both village policy and empowerment, as well as on community participation. However, it was found that village policy and empowerment do not significantly influence community participation. Furthermore, the village policy and empowerment variable was not proven to mediate the relationship between the influence of leadership and the level of citizen participation. These findings indicate that community involvement in the research area remains heavily dependent on the figure and personal instructions of the village leader, rather than the effectiveness of existing regulations or formal empowerment programs. Strengthening transformational leadership capacity is the main key to driving inclusive and sustainable village development.